Arterial Hypertension and Severe COVID-19 in Hospitalized Patients: Data from a Cohort Study - V. I. Podzolkov; A. E. Bragina; A. I. Tarzimanova; L. V. Vasilyeva; E. S. Ogibenina; E. E. Bykova; I. I. Shvedov; A. A. Ivannikov; N. A. Druzhinina (Столичная издательская компания, 2023)
Aim. To assess the association  of hypertension  with the severe forms and fatal outcomes of Coronavirus disease 2019 (COVID-19).Material and Methods. This retrospective  cohort study involved adult patients (≥18 years old),  admitted to the University  hospital №4 of Sechenov University (Moscow, Russia) between 08 April 2020 and 19 November 2020 with clinically diagnosed or laboratory-confirmed COVID-19. The cohort included 1637 patients. The primary outcome was all-cause in-hospital mortality. The secondary outcomes included intensive care unit admission (ICU) and invasive ventilation. Multiple logistic regression was performed to assess the independent association  between risk factors and endpoints.Results. A total of 1637 patients were included in the study. 51.80% (n=848) of the subjects were males. The median age was 59.0 (48.0; 70.0) years and 55.90% (n=915) had pre-existing diagnosis of hypertension. Patients with hypertension  had significantly more severe lung injury based on chest CT scan findings  as well as lower oxygen saturation  (SрO2). More of them were admitted to ICU  and  placed  on invasive  ventilation.  The hypertension  group  also  had  higher  mortality.  Age,  hypertension, glucose, C-reactive protein and decreased platelet count were independently associated with mortality, hypertension  having the strongest association (OR 1.827, 95% CI 1.174-2.846, p=0.008). Age,  hypertension, neutrophil count, platelet count, glucose, and CRP were independently associated  with ICU  admission, with hypertension  having  the strongest  association  (OR  1.595, 95% CI 1.178-2.158, p=0.002). Age, hypertension, glucose, CRP and decreased platelet count were independently associated with invasive ventilation, with hypertension having the strongest association  (OR  1.703, 95% CI 1.151-2.519, p=0.008).Based on the multiple logistic regression models, odds of death, ICU admission, and invasive ventilation were higher in the hypertension  group as compared  to the group without hypertension.Conclusion. Hypertension can be an independent predictor of severe COVID-19 and adverse outcomes, namely death, ICU admission, and invasive ventilation in hospitalized  patients.